Method of detection of dexamethasone in biological tissues and its application to assess the local kinetics of this drug Authors - Dina V. Yunina; Valentin P. Ageev; Andrey V. Zaborovskiy; Larisa A. Tararina; Sergei V. Tsaregorodtsev; Alexander V. Kokorev; Dmitry N. Andreev; Aleksandra E. Pyanzina; Vasilisa I. Shlyapkina; Nikolay A. Pyataev; Oleg A. Kulikov (Belgorod National Research University, 2023)
Introduction: The study of the pharmacokinetics of glucocorticosteroids is often required to solve fundamental and applied tasks of pharmacology. HPLC methods based on ultraviolet detection are attractive due to their availability, but their sensitivity is low enough to study in vivo kinetics. In this study, we propose a method for the determination of dexamethasone in biological objects, based on the use of HPLC with UV detection and having sufficient sensitivity to determine the drug in biological media (blood and periarticular tissues). Materials and methods: Extraction of dexamethasone from biosamples was carried out by liquid-liquid extraction with acetone in an acidic medium using atenolol as an internal standard. The analysis was carried out on a Kromasil-100 C18 column. A mixture of methanol with phosphate buffer in the ratio 50÷50, pH=5.6 was used as the mobile phase. Detector - UV, wavelength - 254 nm. The LLOQ of the method was 50 ng/mL; the calibration curve demonstrated linearity in the con-centration range of 50-1000 ng/mL.The method was used to detect the medicinal product in peri-synovial tissues of rats with an autoimmune arthritis model. Results: This study demonstrated that intraarticular injection of the liposomal form of dexamethasone, compared with its water-soluble form, allows maintaining the active concentration of the product in the joint and periarticular tissues for a longer time, which creates prerequisites for enhancing its therapeutic effect. Conclusion: The proposed method provides a sensitive and specific approach for measuring dexamethasone in biological samples, such as blood and periarticular tissues. Preliminary findings indicate that the liposomal form of dexamethasone may exhibit better pharmacokinetic properties than the water-soluble form, which could lead to improved therapeutic outcomes.